Major Histocompatibility Complex and Malaria: Focus on Plasmodium vivax Infection - Lima-Junior, Josué da Costa; Pratt-Riccio, Lilian Rose (Frontiers in Immunology, 2016)
The importance of host and parasite genetic factors in malaria resistance or susceptibility has been investigated since the middle of the last century. Nowadays, of all diseases that affect man, malaria still plays one of the highest levels of selective pressure on human genome. Susceptibility to malaria depends on exposure profile, epidemiological characteristics and several components of the innate and adaptive immune system that influences the quality of the immune response generated during the Plasmodium lifecycle in the vertebrate host. But it is well known that the parasite’s enormous capacity of genetic variation in conjunction with the host genetics polymorphism is also associated with a wide spectrum of susceptibility degrees to complicated or severe forms of the disease. In this scenario, variations in genes of the Major Histocompatibility Complex (MHC) associated with host resistance or susceptibility to malaria, have been identified and used as markers in host-pathogen interaction studies, mainly those evaluating the impact on the immune response, acquisition of resistance or increased susceptibility to infection or vulnerability to disease. However, due to the intense selective pressure, number of cases and mortality rates, the majority of the reported associations reported concerned Plasmodium falciparum malaria. Studies on the MHC polymorphism and its association with P. vivax, which is the most widespread Plasmodium and the most prevalent species outside the African continent, are less frequent but equally important. Despite punctual contributions, there are accumulated evidences of human genetic control in P. vivax infection and disease. Herein we review the current knowledge in the field of MHC and derived molecules (HLA Class I, Class II, TNF-α, LTA, BAT1 and CTL4) regarding P. vivax malaria. We discuss particularly the results of P. vivax studies on HLA class I and II polymorphisms in relation to host susceptibility, naturally acquired immune response against specific antigens and the implication of this knowledge to overcome the parasite immune evasion. Finally, the potential impact of such polymorphisms on the development of vaccine candidate antigens against P. vivax will be studied.